EX SITU STUDY ON CHEMICAL VARIABILITY OF WORMWOOD (ARTEMISIA ABSINTHIUM L.) - Geszprych, A.; Weglarz, Z.; Kosakowska, O. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Wormwood (Artemisia absinthium L.) is a perennial growing wild in Poland. The herb of this plant is used both in the phytopharmaceutical and food industry as well as in organic agriculture. The application of wormwood extracts depends on their chemical composition, especially the content of bitter and volatile compounds, including thujones regarded as neurotoxins. There are reports indicating intraspecific variability of this species. In our study fourteen populations of wormwood from natural sites in Poland and from four European botanic gardens were compared in respect of the content of biologically active compounds in herb. Plants were grown at the experimental field of the Department of Vegetable and Medicinal Plants of Warsaw University of Life Sciences – SGGW. Herb was harvested in the second year of plant vegetation at the beginning of blooming period. Content of essential oil in the raw material was determined by hydrodistillation method and composition of essential oil by GC. Content of flavonoids and phenolic acids as well as bitterness value were also determined, according to Polish Pharmacopoeia VI (2002). The populations differed considerably in the content of all investigated compounds: essential oil (0.21-0.85%), flavonoids (0.08-0.27%), phenolic acids (0.12-0.25%), and in bitterness value (34,000-83,000). Regarding essential oil composition, the populations represented different chemotypes, with sabinyl acetate, chrysanthenyl acetate, (Z)-myroxide or beta-thujone as a dominant constituent. Only two populations were characterised by a distinct content of thujones in essential oil.